2019
DOI: 10.29271/jcpsp.2019.08.720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adequacy of Dialysis between Single-use and Reused Hemodialyzers in Patients on Maintenance Hemodialysis

Abstract: Objective: To evaluate performance of thin layer agar (TLA) 7H11 method for detection of ofloxacin (OFX) and kanamycin (KM) resistance in smear positive clinical specimens of patients with tuberculosis comparing the results with gold standard MGIT 960 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…These issues are believed to arise from the reprocessing procedure involving sanitizing agents [ 67 , 70 ]. However, two studies have indicated that single, minimal (>6 times), or multiple dialyzer reuse carries no impact on dialysis adequacy, body weight, and serum albumin level [ 71 , 72 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…These issues are believed to arise from the reprocessing procedure involving sanitizing agents [ 67 , 70 ]. However, two studies have indicated that single, minimal (>6 times), or multiple dialyzer reuse carries no impact on dialysis adequacy, body weight, and serum albumin level [ 71 , 72 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…The dialyzer reuse does not seem to affect the effectiveness of dialysis and is a widely used practice in countries with restricted resources. 15,16 In addition, although some studies show that the all-cause mortality in patients undergoing high flux dialysis may be lower compared to low flux hemodialysis, 15,17 this subject is still a matter of controversy. 18 The association of age and higher levels of bicarbonate had already been reported 3,18 and can be interpreted as a consequence of the lower acid generation in the dialysis interval due to the sarcopenia and reduced physical activity that can affect older hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dialyzer reuse does not seem to affect the effectiveness of dialysis and is a widely used practice in countries with restricted resources. 15 , 16 In addition, although some studies show that the all-cause mortality in patients undergoing high flux dialysis may be lower compared to low flux hemodialysis, 15 , 17 this subject is still a matter of controversy. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The highest was in the age range of 65-74 years with the percentage of 8.23‰ (13). In several previous studies related to routine hemodialysis patients, the average age of the research subjects was 43-59 years (9,12,(14)(15)(16)(17)(18).…”
Section: A the Effects Of Reuse Dialyzer Application On Hd Adequacy T...mentioning
confidence: 99%